EFEKTIVITAS PROGRAM KAWASAN RUMAH PANGAN LESTARI (KRPL) DALAM MENDUKUNG KETAHANAN PANGAN RUMAH TANGGA SELAMA PANDEMI DI KOTA KEDIRI - Dellia Ayu Elma Anindya; Desiana Nuriza Putri; Novi Dwi Priambodo (Fakultas Pertanian Universitas Veteran Bangun Nusantara Sukoharjo, 2021)
The KRPL (Sustainable Reserve Food Garden) program is an alternative in realizing food self-sufficiency to achieve food security during the Covid-19 pandemic. This study is to determine the impact of the KRPL program on household food expenditure patterns, food consumption patterns, and consumption levels by using a questionnaire interview method in 8 active KRPL groups in the city of Kediri with a total of 80 respondents. The result of this study indicates that as much as 70% of the harvest in process for the food and nutritional needs of the family, 38.75% think that the yields from their yards can meet their food needs. The yields of each KRPL are different due to several factors, namely, the area of land, the awareness of group members, the weather, and the desire of the members to plant types of plants. From the amount of harvest, it can be seen that the level of success of the KRPL program has a positive impact on household food consumption patterns. A yard or harvest yields are still dominant for household consumption. This condition supports the main concept of the KRPL program, namely to strengthen household food security.